Magnitude of gestational diabetes mellitus, its influencing factors and diagnostic accuracy of capillary blood testing for its detection at a Tertiary Care Centre, Rajkot, Gujarat - Rajesh K Chudasama; A M Kadri; Apurva Ratnu; Mahima Jain; Chandrakant P Kamariya (Wolters Kluwer Medknow Publications, 2019)
Background: Gestational diabetes mellitus (GDM) occurs during pregnancy which affects mother, fetus, and outcome of pregnancy, hence early detection is necessary. The objective of this study was to ascertain the validity of glucometer over standard biochemical testing for detection of GDM and to estimate prevalence of GDM and its associated risk factors. Materials and Methods: A hospital-based study was conducted at Antenatal clinics of Obstetrics Department, tertiary care hospital, based on the "National Guidelines for Diagnosis and Management of GDM." Totally 357 pregnant women between 21 and 28 weeks of gestational age agreed were included in the study from January to March 2016. After obtaining written consent, one step procedure was offered to pregnant women by giving 75 g of anhydrous glucose dissolving in 200-250 ml of water. After 2 h, glucose level was estimated by capillary testing with glucometer and venous glucose by glucose oxidase test. Results: GDM was found in 20.4% pregnant women with capillary testing done by glucometer compare to 11.5% with venous blood testing. GDM was found higher among literates, homemakers, Hindus, people living in nuclear family, belongs to middle class, residing in urban area, primigravidae, obese and with gestational age between 21 and 24 weeks. Intermediate agreement (Kappa = 0.42) was found between two methods with sensitivity of 70.7%, specificity of 86.1%, positive predictive value 39.7%, and negative predictive value 95.8%. Conclusion: Intermediate agreement between two methods indicates glucometer testing can be used to screen pregnant women at an early gestational age (21 weeks), at the community level by health-care workers.